Comparing the anaesthetic efficacy of 1.8 mL and 3.6 mL of anaesthetic solution for inferior alveolar nerve blocks for teeth with irreversible pulpitis: a systematic review and meta‐analysis with trial sequential analysis. (10th November 2020) - Nagendrababu, V.; Abbott, P. V.; Pulikkotil, S. J.; Veettil, S. K.; Dummer, P. M. H.
Abstract: Background: The scientific literature is contradictory in relation to selecting the appropriate volume of local anaesthetic solution for inferior alveolar nerve blocks (IANB) when attempting to anaesthetize mandibular teeth with irreversible pulpitis. Objectives: To compare the efficacy of 1.8 and 3.6 mL of the same anaesthetic solution for IANBs when treating mandibular teeth with irreversible pulpitis. Methods: A literature search was performed in PubMed, Scopus and EBSCOhost databases until May 2020. Randomized clinical trials published in English, comparing 1.8 with 3.6 mL of the same anaesthetic solution for IANBs in permanent mandibular teeth with irreversible pulpitis, were included. The risk of bias of the included trials was appraised using the revised Cochrane risk of bias tool. A meta‐analysis was performed using the random‐effects model. The effect of random errors on the results of the meta‐analysis was evaluated by trial sequential analysis and the quality of evidence was appraised using the Grading of Recommendations, Assessment, Development and Evaluation (GRADE) approach. Results: Four clinical trials involving 280 teeth from patients with ages ranging from 18 to 65 years were included. Among the four trials, three were categorized as having a 'low' risk of bias and one was categorized as having 'some concerns'. The primary meta‐analysis revealed that 3.6 mL of anaesthetic solution when administered for IANBs was associated with significantly greater success rates compared with 1.8 mL (RR = 1.94; 95% CI, 1.07, 3.52; I 2  = 77%). Similarly, the results of the sensitivity analysis (restricting trials only to those that used the Heft‐Parker visual analogue pain scale) revealed that the use of 3.6 mL significantly increased the success of IANBs compared with 1.8 mL. The trial sequential analysis confirmed the evidence for the beneficial effect of 3.6 mL to achieve success for IANBs was 'conclusive'. The quality of evidence was graded as 'high'. Conclusion: Increasing the volume of anaesthetic solution from 1.8 to 3.6 mL improved the success rate for IANBs in mandibular molars with irreversible pulpitis. The quality of the evidence was 'high'. Future high‐quality clinical trials are required with different types of anaesthetic solutions and other types of teeth.